INNATE LYMPHOID CELLS AND FIBROTIC REGULATION - Horsburgh, Steven; Todryk, Stephen; Distler, Jörg; O'Reilly, Steven; Ramming, Andreas (Immunology Letters, 2017)
Innate lymphoid cells (ILCs) are innate immune cells that do not possess B or T cell receptors but belong to the lymphoid lineage. While these cells have not yet been extensively investigated since their classification as a homogenous group, emerging evidence suggests that they exert significant regulatory roles in both tissue remodelling and inflammation, and are therefore, also involved in fibrotic regulation. The following review will serve to outline the transcription factors, surface markers, and cytokines that define each subgroup, and the process by which these cells differentiate. Furthermore, the diverse functions of these cells in non-pathogenic states will be discussed, in addition to the interactions between ILCs and other cells of the immune system, both innate and adaptive, and how these pathways can elicit both pro- and anti-inflammatory and -fibrotic effects in varying tissues.
EVALuna2:13445